Routledge Handbook of Climate Change Impacts on Indigenous Peoples and Local Communities - Reyes García, Victoria (Routledge Environment and Sustainability Handbooks, 2024)
This Handbook examines the diverse ways in which climate change impacts Indigenous Peoples and local communities and considers their response to these changes. While there is well-established evidence that the climate of the Earth is changing, the scarcity of instrumental data oftentimes challenges scientists' ability to detect such impacts in remote and marginalized areas of the world or in areas with scarce data. Bridging this gap, this Handbook draws on field research among Indigenous Peoples and local communities distributed across different climatic zones and relying on different livelihood activities, to analyse their reports of and responses to climate change impacts. It includes contributions from a range of authors from different nationalities, disciplinary backgrounds, and positionalities, thus reflecting the diversity of approaches in the field. The Handbook is organised in two parts: Part I examines the diverse ways in which climate change - alone or in interaction with other drivers of environmental change - affects Indigenous Peoples and local communities; Part II examines how Indigenous Peoples and local communities are locally adapting their responses to these impacts. Overall, this book highlights Indigenous and local knowledge systems as an untapped resource which will be vital in deepening our understanding of the effects of climate change. The Routledge Handbook of Climate Change Impacts on Indigenous Peoples and Local Communities will be an essential reference text for students and scholars of climate change, anthropology, environmental studies, ethnobiology, and Indigenous studies.